2016
DOI: 10.1007/s13277-016-5429-8
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GAS5 inhibits proliferation and progression of prostate cancer by targeting miR-103 through AKT/mTOR signaling pathway

Abstract: In prior research, evidence has been found for a relation between low exposure of long non-coding RNAs (lncRNAs) and prostate tumor genesis. This study aims to clarify the underlying mechanisms of lncRNA GAS5 in prostate cancer (PCa). In total, 118 pairs of PCa tissues and matched adjacent non-tumor tissues were collected. Additionally, lncRNA GAS5 exposure levels were determined using RT-PCR and in situ hybridization. In addition, dual-luciferase report assay was performed to verify the target effect of lncRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 37 publications
6
82
0
Order By: Relevance
“…Autophagy is recognized as a highly conserved bulk protein degradation pathway that accounts for the turnover of long-lived proteins, disposal of injured organelles. 28 Here, blocking mTOR by its antagonist rapamycin engenders not only mTOR inactivation but also the reactivation of autophagy, indicating that GAS5 may blunt cisplatin-triggered autophagy activation in a mTOR-dependent manner. Though abundant research has been made, the role of autophagy during chemoresistance is blurry and even contradictory.…”
Section: Gas5 Mutes Cisplatin-activated Autophagy In a Mtor-dependementioning
confidence: 90%
“…Autophagy is recognized as a highly conserved bulk protein degradation pathway that accounts for the turnover of long-lived proteins, disposal of injured organelles. 28 Here, blocking mTOR by its antagonist rapamycin engenders not only mTOR inactivation but also the reactivation of autophagy, indicating that GAS5 may blunt cisplatin-triggered autophagy activation in a mTOR-dependent manner. Though abundant research has been made, the role of autophagy during chemoresistance is blurry and even contradictory.…”
Section: Gas5 Mutes Cisplatin-activated Autophagy In a Mtor-dependementioning
confidence: 90%
“…PCA3 is relieved sponging of miR‐1261, further led to suppression of the target gene PRKD3 , and thus inhibited cell proliferation of PCa . There were studies revealed that an up‐regulated lncRNA GAS5 inhibited the pathogenesis and progression of PCa through directly targeting miR‐103, and negatively mediated the AKT/mTOR signalling pathway . In addition, published research reported that MEG3 inhibited the progression of gastric cancer through regulating miR‐181 family and its downstream targeting molecule Bcl‐2 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of GAS5 decreased Akt signalling [237,465]. Therefore, lncRNA regulation of Akt signalling seems to highly important in determining the sensitivity of NSCLC cells to the EGFR-TKI gefitinib.…”
Section: Lncrnas Emt and Drug Resistancementioning
confidence: 99%